Pemanfaatan Influencer Berbasis Virtual dalam Komunikasi Pemasaran - Laili Muttamimah; Irwansyah Irwansyah (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2023)
The utilization of virtual influencers is growing along with the advancement of technology. The high demand from brands for collaboration creates an opportunity for virtual influencers to become a profitable business. The presence of virtual influencers raises the question of how effective they are when compared to human influencers, as many brands use virtual influencers to promote products that are targeted for human consumption. This research aims to examine the development of virtual influencer trends, opportunities and challenges, and its future in marketing communication practices. The research approach is qualitative with a case study method. Data was collected using observation and documentation. Three virtual influencer accounts were purposively selected for further analysis. The results showed that the trend of virtual influencers is growing in brand campaigns. Full control, time and cost saving, and flexibility are the opportunities of virtual influencers. However, virtual influencers are considered incapable of displaying emotional reactions and building trust. Even so, the utilization of virtual influencers has the potential to continue to grow in the future, especially in marketing communication practices.